Development of an integrated model for production planning and cell formation in cellular manufacturing systems - Raminfar, Reza (2010)
A cellular manufacturing system (CMS) is a manufacturing structure organized based on the group technology (GT) concept. CMS manufacturing system has many advantages compared to job shop or flow line manufacturing system. The design of CMS involves many structural and operational issues. One of the most important design steps is the formation of part families and machine cells or cell formation problem (CF), another problem is “how to determine the optimal quantities of different part-types” or in the other word production planning problem in CMS.